Patient‐related factors independently impact overall survival in patients with myelodysplastic syndromes: an MDS‐CAN prospective study. (15th March 2016) - Buckstein, Rena; Wells, Richard A.; Zhu, Nancy; Leitch, Heather A.; Nevill, Thomas J.; Yee, Karen W. L.; Leber, Brian; Sabloff, Mitchell; St. Hilaire, Eve; Kumar, Rajat; Geddes, Michelle; Shamy, April; et al.
Summary: Little is known about the effects of frailty, disability and physical functioning on the clinical outcomes for myelodysplastic syndromes (MDS). We investigated the predictive value of these factors on overall survival (OS) in 445 consecutive patients with MDS and chronic monomyelocytic leukaemia (CMML) enrolled in a multi‐centre prospective national registry. Frailty, comorbidity, instrumental activities of daily living, disability, quality of life, fatigue and physical performance measures were evaluated at baseline and were added as covariates to conventional MDS‐related factors as predictors of OS in Cox proportional hazards models. The median age was 73 years, and 79% had revised International Prognostic Scoring System (IPSS‐R) risk scores of intermediate or lower. Frailty correlated only modestly with comorbidity. OS was significantly shorter for patients with higher frailty and comorbidity scores, any disability, impaired grip strength and timed chair stand tests. By multivariate analysis, the age‐adjusted IPSS‐R, frailty (Hazard ratio 2·7 (95% confidence interval [CI] 1·7–4·2), P < 0·0001) and Charlson comorbidity score (Hazard ratio 1·8 (95% CI 1·1–2·8), P = 0·01) were independently prognostic of OS. Incorporation of frailty and comorbidity scores improved risk stratification of the IPSS‐R by 30% and 5%, respectively. These data demonstrate for the first time, the importance of considering frailty in prognostic models and a potential target for therapeutic intervention in optimizing clinical outcomes in older MDS patients. Trial Registration:ClinicalTrials.gov Identifier: NCT02537990.